Panel data estimation of infant mortality rate in the Philippines 1987-2000 - Balabbo, Maria Ligaya Merlux M. (School of Management, University of the Philippines Mindanao, 2005)
The study was conducted to examine the relationship between Infant mortality rate and socio-economic variables such as per capita gross domestic product, income inequality index, per capita health expenditure, cohort survival rate in public and private secondary, total fertility rate and life expectancy at birth. The study utilised a panel data containing 16 regions for cross-sectional data and 14 years from 1987 to 2000 for time series data. Results showed that education was the only factor that can significantly affect infant mortality rate. Philippine infant mortality rate showed a significant improvement over time but compared to other Asian countries the rate is still quite high. Based on infant mortality and its proximate and socio-economic determinants, the current health status of Filipinos can still be improved.